Dropout in youth and adult education: a multilevel analysis of students and schools in Chile - Contreras-Villalobos, Tabata; López, Verónica; Baleriola, Enrique; González, Luis (Frontiers in Psychology, 2023)
School dropout is an increasing and worldwide phenomenon, marked by inequality and educational exclusion. In Chile, many students who have dropped out of regular schools attempt to reenter youth and adult education (YAE). However, some of them drop out again from YAE. The purpose of this study was to identify and jointly analyze school and individual factors that influence dropout in YAE. This secondary multilevel analysis of official datasets from Chile’s Ministry of Education focused on students enrolled in YAE (N = 10,130). Findings show that the individual risk factors of age (19–24 years) and low academic achievement, and the school-level factors of number of teachers (raw and student-to-teacher ratio), available economic resources, and quality of school management contribute to explaining YAE dropout. We discuss the need to develop school-level protective factors that build connections, foster student engagement, and ultimately, promote students´ permanence and progress in YAE